Experimental and numerical investigations of steel-reinforced concrete-filled steel tubular members under compression-bending-shear loads. (June 2021) - Wang, Wen-Da; Ji, Sun-Hang; Xian, Wei; Shi, Yan-Li
Abstract: This paper experimentally and numerically investigated the behavior of the circular steel-reinforced concrete-filled steel tubular (SRCFST) members under compression-bending-shear loads. Ten SRCFST specimens were designed and tested. The factors, i.e., shear-span ratio, the axial compression ratio and the cross-sectional form of steel profile were considered into the tests. Failure modes of specimens, load-displacement curves and load-strain curves derived from the tests were analyzed. The test results show that, the SRCFST specimens exhibit both bending and shear failure modes with distinct degrees, and the combined action between the concrete and steel profile is found. The excellent ductile behavior of specimens is also observed from the load-displacement curves. Furthermore, the effects of shear-span ratio and axial compression ratio on the lateral ultimate capacity were evaluated. Subsequently, the finite element analysis (FEA) model was established to predict the experimental results and further reveal the working mechanism of the specimen under combined compression-bending-shear loads. The verified numerical model was also applied to evaluate the influences of different parameters on the lateral capacity. Finally, the simplified formulae for the lateral ultimate capacity of circular SRCFST members under compression-bending-shear loads were proposed. Graphical abstract: Unlabelled Image Highlights: Very limited studies on the SRCFST members under compression-bending-shear loads are available. Ten SRCFST specimens under combined loads are experimentally investigated. The FEA model is developed to reveal the working mechanism and evaluate the influences of different parameters. The simplified formulae are proposed for predicting the lateral ultimate capacity of SRCFST members.